2017
DOI: 10.5194/tc-2017-178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Study of the Fracturing of Ronne - Filchner Ice Shelf, Antarctica, Using Multisource Satellite Data from 2001 to 2016

Abstract: Abstract. We propose a new framework of systematic fracture mapping and major calving event prediction for the large ice shelves in Antarctica using multisource satellite data, including optical imagery, SAR imagery, altimetric data, and stereo mapping imagery. The new framework is implemented and 10 applied for a comprehensive study of the fracturing of Ronne-Filchner Ice Shelf (RFIS), the second largest ice shelf in Antarctica, using a long time dataset dating back to 1957. New remote sensing data that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The extent of freezing conditions is important because marine ice accretion supports ice shelf stability through its effect on the mechanical properties of ice (Kulessa et al, 2014;McGrath et al, 2014;Li et al, 2017) and by altering the extent of grounding on topographic highs such as ice rises and rumples. Our standard cold tide-forced case produces local maxima in marine ice growth rates in the northwestern RIS, the region northeast and east of Korff Ice Rise, and the region to the north and west of Henry Ice Rise (Fig.…”
Section: Role Of Advection Through South Channelmentioning
confidence: 99%
“…The extent of freezing conditions is important because marine ice accretion supports ice shelf stability through its effect on the mechanical properties of ice (Kulessa et al, 2014;McGrath et al, 2014;Li et al, 2017) and by altering the extent of grounding on topographic highs such as ice rises and rumples. Our standard cold tide-forced case produces local maxima in marine ice growth rates in the northwestern RIS, the region northeast and east of Korff Ice Rise, and the region to the north and west of Henry Ice Rise (Fig.…”
Section: Role Of Advection Through South Channelmentioning
confidence: 99%
“…Liu et al [12] detected sparse crevasse points from three-dimensional ICESat-1/GLAS footprints for large-size crevasses. Other researchers reconstructed three-dimensional information of glacier surfaces using stereophotogrammetry [14][15][16][17], and three-dimensional crevasses can also be captured [18,19]. Although these stereophotogrammetry methods are efficient for the three-dimensional mapping of crevasses, they are still limited by three factors: (1) The difficulty of surveying evenly distributed ground control points; (2) the low contrast of the texture over a glacier surface; and (3) the lack of light at the bottom and sidewalls of a crevasse.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Larsen C Ice Shelf (Mueller et al, 2012) and Pine Island Glacier ice shelf (Schodlok et al, 2012) showed that changes to the ice shelf cavity shape can significantly alter the spatial pattern of basal melt rate, particularly in regions where tidal currents contribute substantially to the total turbulent kinetic energy near the ice base. Tides were not explicitly included in the forcing for the Hellmer et al (2012) study; however, tidal currents often play a critical role in setting the pattern and magnitude of basal melt rates under cold water ice shelves (MacAyeal, 1984;Padman et al, 2018) including FRIS (Makinson et al, 2011), which leads us to hypothesize that tides would influence changes in meltwater production from a warming ocean.…”
Section: Introductionmentioning
confidence: 99%